PENGARUH DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA DINAS PEMBERDAYAAN PEREMPUAN, PERLINDUNGAN ANAK, PENGENDALIAN PENDUDUK, DAN KELUARGA BERENCANA KABUPATEN PASURUAN - Nafiza, Mila Warda; Sutikno, Bambang; Erwantiningsih, Eni (Bhinneka Multidisiplin Journal, 2025)
Employees play an important role in determining the success of an organisation, especially through discipline and communication effectiveness. Absenteeism data for 2024 shows a high level of tardiness which can reduce performance. Communication barriers such as lack of coordination and differences in perception also interfere with task achievement. This study analyses the effect of work discipline and communication on employee performance at DP3AP2KB Pasuruan Regency. The researcher used a quantitative approach with a questionnaire as a data collection tool from 67 respondents representing the entire population. Researchers analysed the data with multiple linear regression to test the simultaneous and partial effects between variables. The results show that work discipline and communication contribute positively and significantly to improving employee performance. Discipline strengthens employees' responsibility towards tasks, while good communication creates a more conducive work environment. This research encourages strengthening the discipline monitoring system and improving the effectiveness of internal communication for performance optimisation